KINERJA KEUANGAN PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA - Veronica, Aries (Fakultas Ekonomi Universitas IBA, 2017)
The purpose of this study was to determine financial performance to stock price ofminning industries at Indonesian Stock Exchange . This research is field research withdata collection techniques using documentation that the sample size is as much as 33emitten. To test the effect of the financial performance to stock price used multipleregression analysis techniques and to test research hypotheses, F test and t test.From the results of calculations using SPSS for Windows version 17, showed that: thevalue of R Square (R2) illustrates that the Stock price (Y), can be explained by thefinancial performance amounted to 65.6%, while the rest 34.4%, can be explained byother factors, which are not included in this study. F Hypothesis test results, obtainedvalue of sig. (98,701)>(0.05), this means that there is influence of the current ratio, totalasset turnover , return on investment, and total debt to total asset ratio together againststock price. While the results of hypothesis testing t as follows: 1) sig. (0.000)< (0.05),which means that there is effect current ratio to stock price; 2) sig.(0.004) < (0.05),which means that there is effect debt to equity ratio to stock price; 3) sig.(0.846) >(0.05), which means that there is no effect total asset turnover to stock price; 4)sig.(0.000) (0.05), which means that there is no effect return on investment to stock price,and 5) sig.(0.700)>(0.05), which means that there is no effect total debt to total assetratio to stock price